Refleksi Metodologis dalam Ilmu Hukum: Meneropong Paradigma Baru untuk Responsivitas Sosial - Furqon Furqon; Riska Fitriya; Imron Nurfatah; Bayu Adhy Nugraha; Achmad Nasyruddin; Firman Adi Candra (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Legal science as a dynamic discipline continues to face demands for adaptation to rapid social changes. This article reflects on conventional legal research methodologies and proposes a new paradigm that is more responsive to contemporary social issues, such as structural injustice, digitalization, and environmental sustainability. Through a reflective-critical approach, this research analyzes the limitations of traditional normative and empirical methods, and explores interdisciplinary integration with social sciences, anthropology, and technology. The proposed new paradigm emphasizes community participation, research ethics, and the tangible social impact of legal studies. The results indicate that socially responsive legal methodologies can strengthen the role of legal science in shaping inclusive policies and social transformation. This article contributes to the development of more contextual and justice-oriented legal methodologies.